Measuring Brand Value through Adoption and Use of Social Media: A case of Taiwanese Global Brands - Chen, Der Chao; Yu, Shih-Yi (Xing Xiao Ping Lun, 2014)
Social media enable users to express themselves as well as to connect with individuals and groups. Many companies have been using social media as a marketing channel to enhance communication with existing and potential customers. However, how companies measure the value of social media for their brand value remains an interesting inquiry. Based on the work of Hodson, Aytekin, and Crawford (2011), this article attempts to consider the relationship between brand value and LPM (Likes per Million) using Taiwan global brands as the study's sample. The authors found Facebook LPM indicators can gauge the success of company's operating result. It also reflects more "like" numbers on Facebook is no guarantee of LPM indicators. Furthermore,this article discusses the relationship between social media and brand value, and offers directions for future research.